Role of various sugars in improving frozen semen quality of Garut ram - Rizal, Muhammad; ., Herdis; Boediono, Arief; Aku, Achmad Selamet; ., Yulnawati (Indonesian Animal Sciences Society, 2006)
Ram spermatozoa are sensitive to extreme changes in temperature during the freeze-thawed process. The present study was conducted to examine the effects of addition of various sugars in Tris extender on sperm cryosurvival of Garut ram. Semen was collected using an artificial vagina from three mature rams once a week. Immediately after initial evaluation, semen was divided into five parts and diluted with Tris extender (control), Tris extender + 0.4% dextrose, Tris extender + 0.4% raffinose, Tris extender + 0.4% trehalose, and Tris extender + 0.4% sucrose, respectively. Semen was loaded in to 0.25 ml mini straw with the concentration of 200 million or 800 million motile spermatozoa per ml. Semen was equilibrated at 5oC for three hours, then frozen and stored in liquid nitrogen for seven days. Quality of processed-semen including percentages of motile spermatozoa (MS), live spermatozoa (LS), intact acrosome cap (IAC), and intact plasma membrane (IPM) were evaluated after dilution, equilibration, and thawing, respectively. Data were analyzed using completely randomized design with five treatments and six replicates. Means were compared significant difference test at 0.05 significant level. Results of this research showed that there was no significantly difference (P>0.05) between treatments for all sperm quality parameters after dilution and equilibration. Mean percentages of post thawing MS, LS, IAC, and IPM for dextrose (54.00; 68.00; 66.60, and 57.83%), raffinose (50.00; 64.33; 61.80, and 61.75%), trehalose (50.83; 65.67; 61.40 and 57.75%), and sucrose (49.00; 66.80; 58.50 and 58.50%) were significantly (P<0.05) higher than control (40.83; 52.67; 54.60, and 49.40%) respectively. In conclusion, addition of 0.4% dextrose, raffinose, trehalose or sucrose in Tris extender are effective in improving frozen semen quality of Garut ram. Key Words: Sugars, Tris extender, Frozen Semen Quality, Garut Ram